Amisulpride and olanzapine combination treatment versus each monotherapy in acutely ill patients with schizophrenia in Germany (COMBINE): a double-blind randomised controlled trial. (April 2022) - Schmidt-Kraepelin, Christian; Feyerabend, Sandra; Engelke, Christina; Riesbeck, Mathias; Meisenzahl-Lechner, Eva; Verde, Pablo-Emilio; Correll, Christoph U; Kluge, Michael; Makiol, Christian; Neff, Andrea; Lange, Christina; Englisch, Susanne; et al.
Summary: Background: Combining antipsychotics is common in schizophrenia treatment, despite evidence-based guidelines generally not recommending such practice. Otherwise, evidence remains inconclusive, especially regarding specific combinations. The trial aimed to test whether a combination of amisulpride plus olanzapine is more effective than either intervention as a monotherapy. Methods: A multicentre, 16-week, randomised, double-blind, controlled trial was done at 16 psychiatric in-patient centres throughout Germany. Inclusion criteria were adults aged 18–65 years with non-first episode schizophrenia or schizoaffective disorder and with a Positive and Negative Syndrome Scale (PANSS) total score of at least 70 and at least two items of the positive symptoms subscale rated at least 4. Patients were randomly assigned to receive 16 weeks of treatment with either amisulpride plus olanzapine, amisulpride plus placebo, or olanzapine plus placebo (1:1:1), and block randomisation was stratified by study site. To keep patients and investigators masked throughout the duration of the trial, amisulpride, olanzapine, and placebo were administered as identical capsules. Flexibly dosed monotherapy of oral amisulpride (amisulpride plus placebo, 200–800 mg per day) or olanzapine (olanzapine plus placebo, 5–20 mg per day) was compared with a combination of amisulpride plus olanzapine. The primary outcome was symptom reduction measured by the PANSS total score after 8 weeks, in the modified intention-to-treat population (all patients randomly assigned to an intervention and receiving at least one study drug dose). As determined a priori, group differences were examined by t tests (Bonferroni-Holm-adjustment) followed by pre-planned Bayesian analyses as well as imputation methods based on mixed models to account for missing values and post-hoc ANCOVA adjusting for PANSS baseline scores. The study was registered on ClinicalTrials.gov, NCT01609153 ; the German Clinical Trials Register, DRKS00003603; and the European Union Drug Regulating Authorities Clinical Trials Database, EudraCT-No. 2011-002463-20. Findings: Between June 15, 2012, and Dec 15, 2018, 13 692 patients were assessed for eligibility. 13 364 patients were excluded (including for not meeting inclusion criteria, declining to participate, or inappropriate reasons for changing pharmacological treatment), and 328 were then randomly assigned to an intervention group. 112 patients were randomly assigned to receive amisulpride plus olanzapine, 109 were randomly assigned to receive amisulpride plus placebo, and 107 were randomly assigned to receive olanzapine plus placebo. 321 patients were analysed for the primary outcome in the modified intention-to-treat population after exclusion of screening failures and patients who did not receive the intervention (110 for amisulpride plus olanzapine, 109 for amisulpride plus placebo, and 102 for olanzapine plus placebo). Among the 321 patients who were randomly assigned to intervention groups and analysed for the primary outcome, 229 (71%) were male, 92 (29%) were female; the mean age was 40·2 years (SD 11·7); and 296 (92%) were White and 25 (8%) were classified as other ethnicity. PANSS total score improved significantly more at 8 weeks in the amisulpride plus olanzapine group (−29·6 [SD 14·5]) than in the olanzapine plus placebo group (−24·1 [13·4], p=0·049, Cohen's d =0·396). A significant difference was not observed in reduction of PANSS total score between the amisulpride and olanzapine group compared with the amisulpride and placebo group (−25·2 [SD 15·9], p=0·095, Cohen's d =0·29). After 8 weeks and 16 weeks, sexual dysfunction, weight, and waist circumference increase were significantly higher for patients receiving amisulpride plus olanzapine than for those receiving amisulpride plus placebo, with no differences in serious adverse events. Two patients died during study participation; one randomly assigned to the amisulpride plus olanzapine group, and one assigned to the olanzapine plus placebo group (both assessed with no relation to treatment). Interpretation: The advantages of amisulpride plus olanzapine have to be weighed against a higher propensity for side-effects. The use of this specific combination therapy could be an alternative to monotherapy in certain clinical situations, but side-effects should be considered. Funding: German Federal Ministry of Education and Research.